2020
DOI: 10.1073/pnas.2012009117
|View full text |Cite
|
Sign up to set email alerts
|

Polyphosphate is an extracellular signal that can facilitate bacterial survival in eukaryotic cells

Abstract: Polyphosphate is a linear chain of phosphate residues and is present in organisms ranging from bacteria to humans. Pathogens such as Mycobacterium tuberculosis accumulate polyphosphate, and reduced expression of the polyphosphate kinase that synthesizes polyphosphate decreases their survival. How polyphosphate potentiates pathogenicity is poorly understood. Escherichia coli K-12 do not accumulate detectable levels of extracellular polyphosphate and have poor survival after phagocytosis by Dictyostelium discoid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 91 publications
3
43
0
Order By: Relevance
“…PolyP also serves as a nucleation source for amyloid proteins ranging from human α-synuclein and Tau to the E. coli biofilm protein CsgA [ 1 , 29 ]. Finally, several recent studies have demonstrated that bacterial polyP can modulate the mammalian immune response [ 30 , 31 ], suggesting an intriguing potential for host–pathogen polyP crosstalk during infection [ 32 ].…”
Section: Introduction: Inorganic Polyphosphate and Polyphosphate Kinase 1 (Ppk1)mentioning
confidence: 99%
“…PolyP also serves as a nucleation source for amyloid proteins ranging from human α-synuclein and Tau to the E. coli biofilm protein CsgA [ 1 , 29 ]. Finally, several recent studies have demonstrated that bacterial polyP can modulate the mammalian immune response [ 30 , 31 ], suggesting an intriguing potential for host–pathogen polyP crosstalk during infection [ 32 ].…”
Section: Introduction: Inorganic Polyphosphate and Polyphosphate Kinase 1 (Ppk1)mentioning
confidence: 99%
“…Extracellular polyP at concentrations ranging from 5 to 15 μg/ml, which correspond to the concentrations of polyP in medium cell density cultures, inhibit the killing of ingested Escherichia coli ( E. coli ) in D. discoideum cells without significantly affecting the ingestion of E. coli or fluorescently labeled heat-killed yeast (zymosan) bioparticles (Rijal et al, 2020). As previously observed for 15 μg/ml polyP, 47, 470, and 705 μg/ml polyP inhibited the killing of ingested E. coli by D. discoideum cells at 24 hours after ingestion (Figure S1I).…”
Section: Resultsmentioning
confidence: 99%
“…It has already been demonstrated that polyP shows biological effects in a chain length-dependent manner (Angelova et al, 2016). Indeed, bacterial long-chain polyP has been shown to potentiate pathogenicity by inhibiting phagosome maturation (Roewe et al, 2020) and interfering with macrophage function (Rijal et al, 2020). Therefore, it is suggested that the response of polyP to inflammation will be different depending on the dose and degree of polymerization.…”
Section: Discussionmentioning
confidence: 99%